The Role of Social Entrepreneurship in Poverty Alleviation - Ernawati S. K; Firdaus W. Suhaeb; Atifah Magfirah (PINISI Discretion Review, 2026)
Inequality in the distribution of social assistance, lack of access to economic resources, and limited employment opportunities further worsen conditions for people living in poverty, including Indonesia. The purpose of this article is to describe and analyze the role of social entrepreneurship as an alternative in efforts to overcome poverty. The study approach uses literature studies through various relevant scientific journals according to the study of the problem. The findings of the study show that social entrepreneurship plays an important role in creating jobs, improving community skills, and encouraging economic independence at the local level, especially through strengthening the Micro, Small, and Medium Enterprises (MSMEs) sector. Social entrepreneurship not only focuses on financial gain, but also incorporates social values in every activity carried out, so that it can have a wider positive impact on the welfare of the community, including in empowering women in rural areas. In addition, social entrepreneurship also serves to increase community involvement in harnessing local potential and strengthen solidarity among community members. The success of social entrepreneurship is influenced by social networks, active community involvement, the ability to innovate, and consistent government policy support. However, its implementation still faces a number of challenges such as limited access to funding, unstable regulations, low entrepreneurial skills, and lack of access to business training. Therefore, collaboration between the government, the private sector, and the community is needed to strengthen the development of social entrepreneurship in order to make a more effective contribution to improving people's welfare and achieving sustainable poverty alleviation.